Avaliação do uso de códons em infecções virais usando como modelo o vírus da Síndrome Respiratória Aguda Grave (SARS-COV-2) - Elisson Nogueira Lopes (2022)
The SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2) outbreak that started in the year 2019 in Wuhan, China has quickly become a global concern. After a few months, the virus was identified all over the world. March 11, 2020, the World Health Organization (WHO) declared the disease caused by SARS-CoV-2 (Corona Virus Disease: Covid-19) a pandemic. The fast viral spread causes the emergence of different variants over time. In the present work, we use a bioinformatics methodology associated with genomic surveillance as a way to elucidate the infectious process caused by this emerging pathogen. For this purpose, all available reference sequences of Betacoronavirus were analyzed and correlated with the availability of tRNAs in the hosts. Our results allowed us to identify a competition mechanism between Betacoronaviruses and their hosts, through codon selection, in addition suggesting eight susceptible hosts as potential reservoirs for SARS-CoV-2. Additionally, we estimated the impact of International Variants of Concern (VOCs) introduced in Brazil, evaluating how the substitution of circulating variants, over time, allowed the increase in the number of cases and deaths. Our results reinforce the need for large-scale implementation of genomic surveillance, to understand variant transmission and to assist in the implementation of rapid containment measures. This methodology applied in this study can be replicated for the characterization of other possible emerging and reemerging pathogens at national and global levels.